CRIMINAL LIABILITY FOR CRIMINAL ACTS OF MONEY LAUNDERING PERFORMED BY CORPORATIONS - Ikka Puspitasari (DUTA BANGSA UNIVERSITY INDONESIA, 2022)
The development of economic globalization as well as technological advances, has the potential for criminal/crime in the economic field carried out by business actors in the form of corporations that can cause losses and victims. in other cases, these developments encourage the emergence of types of economic crime, or corporate crime. One of the main motives of corporate crime lies in fulfilling economic motives in the form of profits or profits carried out illegally or against the law. Money laundering as a form of crime that not only threatens economic stability and the integrity of the financial system, can also endanger the joints of life. society, nation and state. Money laundering is a form of crime that not only threatens economic stability. In Law Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering. Observing Law Number 8 of 2010 in lieu of Law Number 25 of 2003 concerning the Prevention and Eradication of the Crime of Money Laundering.